Me, myself and the other. Interreligious and intrareligious relations in neo-conservative online forums - Elwert, Frederik; Tabti, Samira; Pfahler, Lukas (Religion, 2020)
The Internet can be a place for exchange, but also foster echo chambers of closed world views. This poses interesting questions for the possibility of interreligious dialogue online. The article examines the cases of German Evangelical and Salafist Internet forums which mainly target a specific religious denomination, but nevertheless provide spaces for contact between different religions and denominations. For the study, a combination of quantitative and qualitative text analysis is applied. Quantitative analysis makes it possible to gain an overview of the discussed themes from a large body of text and serves as a basis for sampling smaller textual units for close examination using qualitative content analysis. The analysis yields two primary results: First, intrareligious dialogue plays a particular role for the negotiation of religious identity. Second, interreligious relations reflect the societal positions of both religious groups.